Which Way to Choose for the Treatment of Metastatic Prostate Cancer: A Case Report and Literature Review - Yang, Xiangwei; Jiang, Donggen; Li, Yamei; Zhang, Tianzhi; Xu, Duanya; Chen, Xianju; Pang, Jun (Frontiers in Oncology, 2021)
Background: Prostate cancer (PCa) is the second most common cancer among males in the world and the majority of patients will eventually progress to the metastatic phase. How to choose an effective way for the treatment of metastatic PCa, especially in the later stage of the disease is still confusing. Herein we reported the case of a patient diagnosed with metastatic PCa and conducted a literature review on this issue. Case Presentation: A 57-year-old man with metastatic PCa had been managed by Dr. J.P. since April 2012 when the patient was admitted to the Third Affiliated Hospital of Sun Yat-sen University by aggravating frequent urination and dysuria. The prostate-specific antigen concentration was 140ng/ml and the diagnosis of PCa was confirmed by prostate biopsy, with a Gleason score of 9. Chest CT and bone scan indicated multiple metastases in the lungs and bones. Triptorelin, bicalutamide, and docetaxel were then administered, six cycles later, the metastatic tumors in the lungs disappeared and those in the bones lessened significantly, along with a remarkable reduction in PSA level (< 2ng/ml). Intermittent androgen deprivation was subsequently conducted until August 2018, when the serum PSA level was found to be above 200ng/ml, again docetaxel 75mg/m2 was administered immediately but the patient was intolerant this time. Instead, abiraterone was administered until March 2019 because of intolerable gastrointestinal side-effects and increasing PSA levels. In October 2019, the patient came to our center, a modified approach of docetaxel (Day1 40mg/m2+Day8 35mg/m2) was administered. Luckily, the PSA level decreased rapidly, the bone pain was greatly relieved and no obvious side-effects occurred. However, four cycles later, docetaxel failed to work anymore, the metastatic tumor in the liver progressed. We proposed several regimens as alternatives, but they were soon denied due to the high prices or unavailability of the drugs. In addition, the patient’s condition deteriorated speedily, and can no longer bear any aggressive treatment. Finally, the patient died of multiple organ failure. Conclusion: The experiences of this case provide valuable evidence and reference for the treatment choices of metastatic PCa, in some circumstances modified and advanced regimens may produce unexpected effects.